Review of Laser Powder Bed Fusion of Gamma-Prime-Strengthened Nickel-Based Superalloys - Olutayo Adegoke; Joel Andersson; Håkan Brodin; Robert Pederson (Metals, 2020)
This paper reviews state of the art laser powder bed fusion (L-PBF) manufacturing of γ′ nickel-based superalloys. L-PBF resembles welding; therefore, weld-cracking mechanisms, such as solidification, liquation, strain age, and ductility-dip cracking, may occur during L-PBF manufacturing. Spherical pores and lack-of-fusion voids are other defects that may occur in γ′-strengthened nickel-based superalloys manufactured with L-PBF. There is a correlation between defect formation and the process parameters used in the L-PBF process. Prerequisites for solidification cracking include nonequilibrium solidification due to segregating elements, the presence of liquid film between cells, a wide critical temperature range, and the presence of thermal or residual stress. These prerequisites are present in L-PBF processes. The phases found in L-PBF-manufactured γ′-strengthened superalloys closely resemble those of the equivalent cast materials, where γ, γ′, and γ/γ′ eutectic and carbides are typically present in the microstructure. Additionally, the sizes of the γ′ particles are small in as-built L-PBF materials because of the high cooling rate. Furthermore, the creep performance of L-PBF-manufactured materials is inferior to that of cast material because of the presence of defects and the small grain size in the L-PBF materials; however, some vertically built L-PBF materials have demonstrated creep properties that are close to those of cast materials.